Immune status in pregnant women against Mycobacterium tuberculosis: A scoping review - Adzkia, Qonita; Maria Jeniffer Ann Siburian; Yunivita, Vycke (Published by Universitas Gadjah Mada, 2026)
Tuberculosis (TB) is a major global health concern, especially in vulnerable populations, such as pregnant women. Changes in the immune system in pregnancy may impair the individual’s ability to withstand this infection. The objective of this scoping review was to systematically map the available literature regarding alteration of the immune response, specifically cytokines profiles, in pregnant women with or without TB. We conducted a systematic search of four databases (PubMed, EBSCO, ScienceDirect, and Scopus). Studies reporting on cytokine measurements in pregnant women with TB were included. Two reviewers independently screened titles/abstracts and full texts against predefined eligibility criteria. Data were charted on study characteristics, population, and reported cytokine outcomes. From 1.320 records, 14 studies were ultimately included based on the exclusion and inclusion criteria. Pregnant women with TB were shown to have reduction in adaptive proinflammatory response, mainly by the decrease of IFN-γ and IL-2 levels in the latter stage of pregnancy. However, this still remains conflicted due to several studies that state otherwise. Other cytokines, such as IL-6 and IL-17, and TGF-β, show a notable depletion in the concentration suggesting the enhancement of the vulnerability of pregnant individuals. Interestingly, there is a rise in the number and function of innate immune cells, which can be seen from the elevated levels of proinflammatory cytokines, including IP-10, MCP-2, and antiinflammatory cytokine, which is IL-1ra. This scoping review provides an overview of the current evidence landscape. It highlights methodological heterogeneity and inconsistent reporting as major challenges in drawing definitive conclusions. The findings underscore the need for more standardized, longitudinal studies to clarify the immune dynamics in pregnant women with TB. This map can guide future primary research and systematic reviews.